A study on the English collocation containing the verb SET with reference to their Vietnamese equivalents / Nguyễn Thị Toàn; NHDKH Assoc. Prof. Dr. Hoàng Tuyết Minh - Nguyễn, Thị Toàn
This study finds out some major points such as: - Syntactically, there are seven types of sentence structure containing the verb Set collocation. There, the structure SVO is the most common with 26.20%. In both English and Vietnamese, there are some similarities between the structures, however some English structures containing the verb Set collocation are changed in Vietnamese. - Semantically, there are many different meanings of the English collocation containing the verb Set, however, the meaning of placing in position is the most common. There are some similarities and differences between the meaning of the English colocation containing the verb Set and their Vietnamese equivalents. In the end, suggesting some implications for teaching and learning English collocation in general and the English collocation containing the verb Set in particular.